New perspectives on the Internet : comprehensive - Schneider, Gary P. , 1952-; Evans, Jessica , 1967- (New perspectives, 2010)
New perspectives on the internet has been updated to cover the newest software including Windows 7, Internet Explorer 8, Mozilla Firefox 3, and Google Chrome. With the new perspectives critical-thinking, problem-solving approach, you will learn basic to advanced features of the Internet - from browser basics to electronic commerce